Las oscilaciones climáticas recientes en Zaragoza (1865-1984) - Cuadrat Prats, José María (Geographicalia, 2017)
Zaragoza’s temperatures -during the last 120 years of observations- have experienced a significant increase till 1950. Then the tendency changes and, while the maximum temperatures begin to fall, the minimun ones keep going up, particularly throung the winter. Explanation to this phenomenon lies in the climatic evolution followed by the North hemisphere and in a possible urban influence.